KEPUTUSAN WISATAWAN DI HOTEL SWISS BELINN-SKA PEKANBARU - Greatsby Yudhistira Ramadhan; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The purpose of conducting this research is to know factors-factors affecting the traveler decisions at swiss belinn-ska hotel and for know dominant factors affecting traveler decisions. This research uses descriptive quantitative methode to analyze the problems. The sampel of this research was 50guests respondences. and, From factors affecting the traveler decisions are 5sub variables they are product, price, location, and hotel promotions. Based on the research that has been conducted, respondents agree with five factors that affecting the decision of tourists get results agree, travelers or tourists give a good response and the dominant factors is location. Keywords : traveler decisions, swiss belinn-ska